The curator : a novel - King, Owen (Scribner, 2023)
Searching for the truth behind the secret she's long concealed, Dora, a former domestic servant, is given curatorship of The National Museum of the Worker by her lover, a place that isn't at all what it seems as she unravels a monstrous conspiracy that brings her to the edge of worlds.